Exploring the impact of hyperlipidemia on cardio-motor function and exercise adaptability in Hispanic-Latinos living with HIV - Rosario, Martin G; McConnell, Rebekah; Redding, Steven (Journal of Sports Research, 2024)
HIV may precipitate a myriad of health-related complications, potentially culminating in disabilities that detrimentally affect the quality of life. Certain conditions, such as hyperlipidemia (LP), which are exacerbated by HIV, can pose additional difficulties for this particular demographic. The aim of this study is to investigate the influence of LP on the cardio-motor profile of Hispanic Latinos living with HIV. The methodology of this study consisted of a submaximal cardiovascular assessment (Ross Test) to collect relevant cardio-motor data for this research. These data were sourced from the records of individuals registered at La Perla de Gran Precio Community Centre for HIV in San Juan, Puerto Rico. The motor profile captured included treadmill speed and incline. Cardiovascular parameters recorded were blood pressure and heart rate at the cessation of the Ross Test. A total of 291 participants were classified into 229 in the non-LP group and 62 in the LP group. The findings of this study showed similar average CD4 counts. An ANOVA analysis revealed significant differences (P < 0.05) in the LP group, including decreased cardio time and treadmill incline compared to their counterparts. Hispanic Latinos living with HIV and LP exhibit notable deficits in motor gait. Gait parameters are particularly compromised in individuals affected by both conditions. The practical implication is to alert healthcare providers to integrate the specific cardio-motor assessments discussed in this study to address the factors influencing gait, which in turn may impact the quality of life of those with HIV.